Prevalence and Predictors of Maternal Alcohol Consumption in Two Regions of Ukraine - Chambers, Christina D. (2014)
BACKGROUND: Fetal Alcohol Spectrum Disorders (FASD) are thought to be a leading cause of developmental disabilities worldwide. However, data are lacking on alcohol use among pregnant women in many countries.. The purpose of this study was to evaluate the prevalence and predictors of alcohol consumption by pregnant women in Ukraine. METHODS: Cross sectional screening of pregnant women was conducted in two regions of Ukraine during the recruitment phase of an ongoing clinical study that is part of the Collaborative Initiative on Fetal Alcohol Spectrum Disorders (CIFASD). Women attending a routine prenatal visit at one of two participating regional centers were asked about alcohol consumption. Quantity and frequency of alcoholic beverages consumed in the month around conception and in the most recent month of pregnancy were measured using a standard interview instrument. RESULTS: Between 2007 and 2012, 11,909 pregnant women were screened on average in the second trimester of pregnancy. Of these, 92.7% reported being ever-drinkers. Among ever-drinkers, 54.8% reported drinking alcohol in the month around conception, and 12.9% consumed at least three drinks on at least one day in that time period. In the most recent month of pregnancy, 46.3% continued to report alcohol use and 9.2% consumed at least three drinks per day. Significant predictors of average number of drinks or heavier drinking per day in either time period in pregnancy included lower gravidity, being single, unmarried/living with a partner, or separated, lower maternal education, smoking, younger age at initiation of drinking and higher score on the TWEAK screening test for harmful drinking. CONCLUSIONS: These findings support the need for education/intervention in women of childbearing age in Ukraine, and can help inform targeted interventions for women at risk of an alcohol exposed pregnancy. The initiation of a standard screening protocol in pregnancy is a step in the right direction.